A Review of Different Curriculums for Effective Teaching Practices [In English] - Sarah Risha (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2021)
As a teacher of more than 20 years and as a curriculum developer, I found out that there are many commonly used teaching methodologies that are not related to our students. This does not mean that what we explain to them is useless. No, but it is that our students do not see the use of information presented to them which leads them to think of it as irrelevant to their lives especially with the new technologies and growing globalization world around us. In this article, I will introduce the two most common types of curriculum instructions which are: linear and holistic approaches in education. I will start with a short introduction to each approach and will present some explanation and discussion platform towards the characteristics of each methodology. Later, I will introduce some best practices that can be utilized in holistic approach classes to help teachers in developing their daily teaching practices. In this article, best practices refer to in-class teacher’s activities, methods or approaches used to improve students’ academic abilities, ways of thinking and desired outcomes. These methods will help students to connect what they learn with their daily lives.